Aplikasi Monitoring Stok Ikan Laut dengan Algoritma FIFO untuk Efisiensi Manajemen Stok - Setiawan, Ridwan; Hestiyanti, Mita; Jianul Hayat, Encep (Jurnal Algoritma, 2025)
PT Berkah Wahana Samudera Jaya Group is a company engaged in the fish trade. In the current business processes of PT Berkah Wahana Samudera Jaya Group, the process involves recording, transferring data to Excel, and monitoring stock manually through Excel, which often causes discrepancies between the actual and recorded stock quantities. The purpose of this study is to design a web-based marine fish stock monitoring application with the implementation of the First In First Out (FIFO) algorithm to ensure that the fish that enters first will be the first to leave, thereby reducing the risk of fish quality deterioration, monitoring stocks more quickly, and ensuring that stock data is always up to date. The research uses the Rational Unified Process (RUP) methodology, which includes four stages of application design, namely Inception, Elaboration, Construction, and Transition, with Unified Modeling Language (UML) system modeling. The result of this research is a stock monitoring application implemented at PT Berkah Wahana Samudera Jaya Group to support fish stock management and minimize recording errors. The contribution of this research is to provide a digital solution that can be used as a reference for developing web-based inventory management systems in the fisheries sector, supporting the transformation of the fisheries industry towards a more efficient, transparent, and integrated digital ecosystem.